Industrial training report at Pejabat Tanah Muar / Nur Natasha Kasim - Kasim, Nur Natasha (Faculty of Business and Management, 2023)
Industrial training (MGT666) is for all undergraduate programs in the Faculty of Business and Management's final course. Students should take the training on dealing with the actual work environment after graduating from the university soon. In the end, they should be able to gain practical knowledge and job skills to develop his or her knowledge, skills, and capacities in organizations certified by the faculty's Industrial Training Unit. My six-month industrial training experience was at Pejabat Tanah Muar, Johor. This internship's report main goals are to analyse the company's strengths, weaknesses, opportunities and threats. During my six-month industrial training at Pejabat Tanah Muar, 1 had been assigned to different departments which are Administration & Financial Department, Revenue Department, Development & Disposal Department, Registration Department and Technical & Enforcement Department. Every month, I was required to change departments so that I could experience different tasks in different departments. It was a lot of fun since I met and engaged with new people. Furthermore, I managed to perform different tasks and develop my skills while I was at my practical place. I learned a lot of things, such as how to interact with the public, how to handle the event, and also how employees did their tasks. Throughout my industrial training at Pejabat Tanah Muar, I can identify their strengths, weaknesses, opportunities and threats using SWOT analysis, then give some recommendations and conclusions on how to fix the problem.